The Effect of Workload on Role Stress and Burnout - Ratna Sari Dewi; I Gede Riana (Journal of Multidisciplinary Academic, 2019)
The success of a company is largely determined by the services provided. The company always trying to improve the employees performance with a hope that the company's goals. Employees are not merely objects in achieving goals, but also become a planners, implementer and controllers who always play an active role in realizing the company's goals, and have thoughts, feelings and desires that can affect their attitude towards work. The organization wants employees who willing to do tasks that are not listed in their job descriptions without any sense of pressure. This study aims to analyse the effect of workload on role stress with burnout as a mediating variable. This study we use questionnaire instrument 74 respondents (employees). The result shows that the relationship between workload on burnout was not significant. The effect between workload on role stress has a significant. The relationship between role stresses on burnout has a significant. Furthermore, the workload has significance effect burnout when the employee felt role stress.